Practice of Girl Child Circumcision in Northwestern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Female circumcision (FC) is still common in many developing countries including Nigeria despite its adverse health consequences. It is performed on women and young girls. This study examined the current awareness and practice of FC in northwestern Nigeria.Patients and Methods:This cross-sectional study was conducted among mothers at a paediatrics department of a tertiary hospital in Kano, northwestern Nigeria. A questionnaire seeking information on the awareness and practice of FC was administered to selected mothers by the researcher. The data was analyzed.Results:Awareness of FC was 93.6% among 234 mothers enrolled in the study. It was practiced by 135 (67.2%) of 201 mothers who had at least one daughter, and only 10.4% of them believed FC was harmful. It was decided by fathers (82.2%), done on babies in the first 7 days (95.6%), by traditional barber (97.0%) and at home (97.8%). Culture was the main reason (69.6%) for performing FC.Conclusion:FC is still commonly practiced. Knowledge of its adverse effects is scanty. More awareness campaigns and effective legislations are needed to curtail this harmful practice.